A preliminary study on the role of personal history of infectious and parasitic diseases on self-reported health across countries - Pfuhl, Gerit (2025)
Objectives: Infectious diseases are often associated with decline in quality of life. The aim of this study is to analyze the relationship between personal history of communicable, i.e., infectious and parasitic diseases and self-rated health. Study design: Secondary analysis of a large dataset multi-country observational study. Methods: We used a four-pronged analysis approach to investigate whether personal history of infectious and parasitic diseases is related to self-reported health, measured with a single item. Results: Three of the four analyses found a small positive effect on self-reported health among those reporting a history of pathogen exposure. The meta-analysis found no support but large heterogeneity that was not reduced by two classifications of countries. Conclusion: Personal history of infectious and parasitic diseases does not reduce self-reported health across a global sample.